Transcatheter aortic valve implantation versus surgical aortic valve replacement: A meta-analysis of randomized controlled trials. (1st December 2016) - Indraratna, Praveen; Tian, David H.; Yan, Tristan D.; Doyle, Mathew P.; Cao, Christopher
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has become a widely utilized method of treatment of severe aortic valve stenosis. The present meta-analysis included all published relevant randomized controlled trials (RCTs) and aimed to compare the safety and efficacy of TAVI compared to surgical aortic valve replacement (AVR). Method: Nine electronic databases were comprehensively searched. Eligible studies were required to be randomized controlled trials which reported comparative endpoints on both TAVI and AVR. Results: Five published RCTs were included in the meta-analysis. A total of 3828 patients were studied. The overall mortality and stroke rates at 30 days and 1 year were not significantly different between TAVI and AVR. Patients undergoing TAVI were more likely to experience vascular complications, aortic regurgitation and permanent pacemaker insertion, however, they were less likely to encounter acute renal failure and major haemorrhage. Conclusions: The data suggest that TAVI is a safe and efficacious alternative to surgical aortic valve replacement in judiciously selected patients.